Analisis dan Evaluasi Proses Bisnis Pada CV.PASTIJADI dengan Menggunakan Konsep Vertikal Abstraksi - Nathania Hutajulu; Aditya Rachmadi; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
CV.PASTIJADI is one IT company under of PT.Talenta Inti Global Madani that located in Surabaya. Director CV.PASTIJADI said that activity for handling client doesn't have a procedure which is some activity resulted in repeated with same goals and the ineffectiveness while working with worker. This research aims to analyze business process (as-is), evaluated that business process, and give a recommendation based on evaluation. This research using some techniques are vertical of abstraction, functional decomposition, value shop, and RACI Chart mapping for analyze. Second, this research using BPMN techniques for modeling the business process, and then this research using FMEA technique for evaluate the business process and last this research using BPI with 12 streamlinng technique for get the recommendation of business process. This research give a result in current business process on analysis of client requirement have reached 26.93%.